2016
DOI: 10.1007/s12035-016-0213-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: the Emerging Class of Non-coding RNAs and Their Potential Role in Human Neurodegenerative Diseases

Abstract: The exciting world of research with RNAs has to its credit some breakthrough findings that led to newer insights on multiple problems including that of human diseases. After the advent of siRNA, microRNA, and lncRNA, exciting novel molecules called circular RNAs (circRNAs) have been recently described. circRNAs are a class of non-coding RNAs, which are produced by scrambling of exons at the time of splicing. They are primarily produced in the brain region and are naturally present inside the cell. The best kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 78 publications
3
95
0
Order By: Relevance
“…In recent years, circular noncoding RNA (circRNA) which is originally thought to be genomic noise has been demonstrated to have vital biological efficacies (Kumar, Shamsuzzama, Haque, Baghel, & Nazir, 2017). Numerous studies have demonstrated that circRNAs can play a regulatory part in the translation and binding of miRNAs and so forth (Beermann, Piccoli, Viereck, & Thum, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, circular noncoding RNA (circRNA) which is originally thought to be genomic noise has been demonstrated to have vital biological efficacies (Kumar, Shamsuzzama, Haque, Baghel, & Nazir, 2017). Numerous studies have demonstrated that circRNAs can play a regulatory part in the translation and binding of miRNAs and so forth (Beermann, Piccoli, Viereck, & Thum, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aberrant circRNA expression is related to 68 human diseases , including human cancers (Meng et al 2017), neural 69 degenerative diseases (Kumar et al 2017), hematological malignancies (Bonizzato et al 2016), 70 and infectious diseases (Qian et al 2018). However, these conclusions might be preliminary and premature, since the circRNA profiles 82 examined in these studies were derived from relatively small datasets, such as RNA sequencing 83…”
mentioning
confidence: 99%
“…Both mechanisms work together to promote VEGFB expression, which ultimately mediates the physiological process of neuropathic pain (61) ( Table 1). Moreover, circRNAs are associated with myotonic dystrophy and amyotrophic lateral sclerosis (ALS) (80).…”
Section: Circrnas In the Neurological Diseasesmentioning
confidence: 99%